EVALUATION OF THE USE OF REACH TRANSMISSIVITY TO QUANTIFY EXCHANGE BETWEEN GROUNDWATER AND SURFACE WATER - Nemeth M.S.; Solo-Gabriele H.M. (My University, 2003)
A method to quantify the exchange of water between surface water channels and the groundwater aquifer based on the concept of reach transmissivity was evaluated for use under transient conditions and incorporated into a numerical model. This method provides significant benefits relative to the common existing method of calculating leakage, which assumes flow of water through a discrete, low permeability layer at the bed of the surface water channel. The reach transmissivity leakage relationship employs input parameters that are more commonly available from published sources, which reduces the effort required for model calibration; also, the calibrated values of the reach transmissivity relationship input parameters are less dependent on model grid spacing. Furthermore, the reach transmissivity relationship allows calculation of flow to each side of the surface water channel, rather than calculating only the net exchange between the surface water and groundwater systems. The reach transmissivity leakage relationship is based on the assumption of steady state conditions; a method was developed to estimate the error associated with its use to simulate transient conditions. The reach transmissivity relationship was further evaluated through its use in analytical and numerical models to simulate conditions in a field study area.
Keywords: SURFACE WATER; GROUNDWATER; LEAKAGE; SEEPAGE; NUMERICAL MODEL